PENGARUH PEMBELAJARAN DARING MENGGUNAKAN WHATSAPP GRUP TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN BIOLOGI IAIN KENDARI DITINJAU DARI KESADARAN METAKOGNITIF - Andi Nurannisa Syam; Syarif Rizalia (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2021)
This study aims to determine the effect of online learning through WhatsApp on student’s learning outcome of biology education IAIN Kendari considering metacognitive awareness. This study is a quantitative type of quasi-experimental research with a 1x3 experimental design. This research was conducted in October 2020, with a population of fifth-semester students of biology education, and the sample consisted of one class, namely class B, which was given treatment. The data were analyzed using SPSS for Windows Software. The technique in taking the sample was Cluster Random Sampling. The results revealed a positive influence on the application of online learning through WhatsApp on student’s learning outcome consideration of metacognitive awareness. The finding also proves that high metacognitive awareness students have better learning outcomes than students with middle and low metacognitive awareness. Keywords: online learning, WhatsApp, learning outcome. metacognitive awareness.